USE OF HEMATOPOIETIC GROWTH FACTOR IN THE MANAGEMENT OF HEMATOLOGICAL SIDE EFFECTS ASSOCIATED TO ANTIVIRAL TREATMENT FOR HCV HEPATITIS - Paola Mancino; Katia Falasca; Claudio Ucciferri; Eligio Pizzigallo; Jacopo Vecchiet (Mediterranean Journal of Hematology and Infectious Diseases)
Haematological abnormalities are common during combination antiviral therapy for chronic hepatitis C. Although dose reduction or discontinuation can easily treat these side effects, they can adversely affect the efficacy of combination antiviral therapy reducing the likelihood of a sustained viral response (SVR). To avoid potentially diminishing a patient’s chance of response, many physicians have begun using growth factors off-label to manage anaemia and neutropenia in hepatitis C. Haematopoietic growth factors are generally well tolerated and they may be useful for managing haematological side effects of anti-HCV therapy improving patients’ quality of life. To date, the role and benefit of these agents during anti-HCV therapy and their positive impact on SVR have not conclusively determined in the published studies. However, the possibility of a benefit to individual outpatients remains, and an individualized approach is recommended. This review explores the incidence, clinical significance, and management of anaemia, neutropenia and thrombocytopenia associated with combination therapy for HCV infection.